Direct and indirect effects of grazing constrain shrub encroachment in semi‐arid Patagonian steppes - Cipriotti, Pablo Ariel (2011)
Question: What are the long-term effects of grazing exclusion on the population structure and dynamics of, and interactions among, three dominant shrub species? Location: Grass-shrub Patagonian steppe, Chubut, Argentina. Methods: Permanent plots were established in grazed paddocks and paddocks excluded from grazing in representative Patagonian rangelands. Shrub abundance, population size-structure, short-term (two 3-yr periods) and long-term (matrix models) population dynamics, and neighborhood interactions of three native and codominant shrub species (Mulinum spinosum, Senecio filaginoides and Adesmia volckmanni) were measured and analysed using different statistical approaches. Results: The total density of shrubs was 74% higher in paddocks excluded from grazing, owing mainly to increases in Mulinum (80%) and Senecio (68%) species. However, differences in size structure between ungrazed and grazed paddocks were only detected in Mulinum. Demographic rates differed between shrub species, time-periods and grazing conditions. In particular, recruitment in the short term (especially in wet years) and population growth rate in the long term (l) were higher in paddocks excluded from grazing only in Mulinum populations. Senecio populations showed a marginal increase in recruitment and mortality independent of the grazing condition in the wet and dry period. Grazing exclusion modified the balance of neighborhood interactions among the three shrub species. In grazing-exclusion paddocks, there was a balance between positive and negative interspecific interactions, while in grazed paddocks there were more negative intraspecific and interspecific interactions, resulting in a net negative balance of neighborhood interactions. Conclusions: Our understanding of woody encroachment in arid rangelands can be informed through evaluation of direct and indirect effects of grazing exclusion on the abundance and demography of dominant woody species. In Patagonian arid steppes, the occurrence of woody encroachment in rangelands excluded from grazing can be explained by altered responses in plant-animal and plant-plant interactions among shrub species.